The Role of Christian Religious Education and Family Interaction in Shaping a Culture of Quality in Leadership Character Development - Mike Makahenggang; Hotmaulina Sihotang (International Perspectives in Christian Education and Philosophy, 2025)
In today's world, the crisis of moral integrity and low quality of leadership have become one of the most serious challenges in education and social life. This study aims to examine how Christian Religious Education and family interactions contribute to the formation of a culture of quality that supports the growth of leadership character based on faith, responsibility, and a spirit of service. The approach used is a reflective literature study with a review of eleven journals, sixteen books or other sources from theological and educational philosophy perspectives, and leadership studies. The results of the study show that Christian Religious Education not only fosters spiritual awareness and ethical thinking skills, but also strengthens students' commitment to excellence as a manifestation of living faith, hence the emphasis is on the active role of parents. The integration of faith education and family interaction creates a culture of quality that encourages continuous growth, self-reflection, and integrity in leadership. The novelty in this study is the formation of an integrated culture of quality.